Psoriasis Severity Assessment Combining Physician and Patient Reported Outcomes: The Optimal Psoriasis Assessment Tool - Leonardi, Craig (Dermatol Ther (Heidelb), 2021)
INTRODUCTION: Psoriasis Area Severity Index (PASI) assessment is complex and time-consuming. A simpler assessment measure more sensitive to changes in symptom severity and predictive of patients’ quality of life (Dermatology Life Quality Index, DLQI) is needed. This study aims to evaluate the Optimal Psoriasis Assessment Tool (OPAT) as an alternative to PASI. METHODS: This integrated analysis of three UNCOVER trials (NCT01474512, NCT01597245, and NCT01646177) randomized patients (N = 3866) with moderate-to-severe psoriasis to subcutaneously administered ixekizumab 80 mg Q2W or Q4W, or placebo or etanercept 50 mg Q2W. Pearson correlations were computed for clinical and patient-reported measures with PASI and DLQI. RESULTS: As the correlations with PASI and BSA were high and not much higher when adding severity, body surface area (BSA) was used for the clinical measure. BSA was the main measure influencing OPAT. Week 12 regression analyses results showed that PASI had a higher correlation with BSA combined with patient assessments than with BSA alone. Sensitivity analyses were also completed for PASI 75 and 90. For DLQI, correlations with the combined measures were even stronger than with BSA alone. A comprehensive model selection procedure was conducted, which illustrated that the two-term models are preferred. CONCLUSION: The OPAT is a simple and time-saving alternative to PASI. It can be derived using BSA and patient-reported assessments having strong correlation with PASI and moderate correlation with DLQI. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13555-021-00544-6.